2021
DOI: 10.4254/wjh.v13.i4.504
|View full text |Cite
|
Sign up to set email alerts
|

Dried blood spot sampling as an alternative for the improvement of hepatitis B and C diagnosis in key populations

Abstract: BACKGROUND To achieve the elimination of hepatitis B and C, there is an urgent need to develop alternative strategies to increase the access of diagnosis, particularly among key populations such as people living with human immunodeficiency virus (HIV), individuals with coagulopathies and chronic kidney disease (CKD) patients. AIM To evaluate the use of dried blood spot (DBS) in the detection of hepatitis B virus (HBV) and hepatitis C virus (HCV) markers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…A recent study performed by Bunthen et al 11 in Cambodia showed a high diagnostic accuracy of DBS for hepatitis B markers in pregnant women and their babies. This was consistent with other studies that performed large‐scale screenings using DBS samples to detect other serological markers (HBsAg and anti‐HBc) from newborns, 12 illegal miners 13 and at‐risk populations 14 . However, no systematic review exists to synthesize the available literature on this topic.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…A recent study performed by Bunthen et al 11 in Cambodia showed a high diagnostic accuracy of DBS for hepatitis B markers in pregnant women and their babies. This was consistent with other studies that performed large‐scale screenings using DBS samples to detect other serological markers (HBsAg and anti‐HBc) from newborns, 12 illegal miners 13 and at‐risk populations 14 . However, no systematic review exists to synthesize the available literature on this topic.…”
Section: Introductionsupporting
confidence: 88%
“…Some studies solely examined newborns, infants, or children ( n = 5) without including their mothers, 12,73–76 while others focused on pregnant women ( n = 3) 77–79 . Three studies ( n = 3) were conducted on adults, 54,75,80 and two studies ( n = 2) each targeted students in high school or university, 78,81 as well as populations with complications such as coagulopathies, chronic kidney disease and syphilis 14,40 . Notably, one study ( n = 1) investigated individuals occupationally exposed to BBVs, specifically hairdressers 82 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential use of DBS, as an alternative sample material, for the detection of HBV markers of infection has been explored [ 6 10 ]. The aim of this study was to further evaluate the feasibility of using DBS for detection of HBsAg, total anti-HBc, HBeAg, and HBV DNA.…”
Section: Introductionmentioning
confidence: 99%